2018
DOI: 10.1038/s41467-017-02621-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Barrett’s esophagus through space and time at single-crypt and whole-biopsy levels

Abstract: The low risk of progression of Barrett’s esophagus (BE) to esophageal adenocarcinoma can lead to over-diagnosis and over-treatment of BE patients. This may be addressed through a better understanding of the dynamics surrounding BE malignant progression. Although genetic diversity has been characterized as a marker of malignant development, it is still unclear how BE arises and develops. Here we uncover the evolutionary dynamics of BE at crypt and biopsy levels in eight individuals, including four patients that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
(58 reference statements)
7
53
0
Order By: Relevance
“…81 Although BE is a premalignant condition conferring predisposal to esophageal adenocarcinoma 82 and previous sequencing studies have shown high prevalence of cancer gene mutations shared between paired dysplastic BEs and esophageal adenocarcinomas, 83,84 few genetic aberrations responsible for de novo BE development have been identified. 85 In line with the acquisition of the intestine-like properties at histologic and gene expression levels, 86 human BE organoids could be maintained in a culture condition similar to that for human intestinal organoids composed of Wnt-3A, R-spondin1, EGF, FGF10, Noggin, and inhibitors of TGF-b and p38 MAPK. 9 BE organoids harbored goblet cells positive for periodic-acid Schiff staining, the hallmark of BE.…”
Section: Esophagusmentioning
confidence: 99%
“…81 Although BE is a premalignant condition conferring predisposal to esophageal adenocarcinoma 82 and previous sequencing studies have shown high prevalence of cancer gene mutations shared between paired dysplastic BEs and esophageal adenocarcinomas, 83,84 few genetic aberrations responsible for de novo BE development have been identified. 85 In line with the acquisition of the intestine-like properties at histologic and gene expression levels, 86 human BE organoids could be maintained in a culture condition similar to that for human intestinal organoids composed of Wnt-3A, R-spondin1, EGF, FGF10, Noggin, and inhibitors of TGF-b and p38 MAPK. 9 BE organoids harbored goblet cells positive for periodic-acid Schiff staining, the hallmark of BE.…”
Section: Esophagusmentioning
confidence: 99%
“…Instead, OAC is a highly copy number (CN) driven disease characterized by early and frequent genomic instability [22][23][24][25][26] . As ongoing genomic instability leads to a large extent of clonal diversity, multiple investigations have therefore focused on the heterogeneity of BE tissues 27 , and high levels of diversity has been associated with a higher risk of progression [28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…The concept is based on measuring both the extent and speed of genetic evolution as a proxy of how “close to cancer” the cells have become ( 136 ). Tissue age is difficult to measure in vivo , but can be estimated with computational methods like Bayesian inference that have been used in molecular clocks applied to somatic epigenetic ( 137 ) and genomic ( 138 ) data from non-dysplastic Barrett's esophagus, a precursor of esophageal adenocarcinoma that is characterized by intestinal metaplasia, driven by chronic acid- induced inflammation ( 139 ).…”
Section: Evolutionary Biomarkers: a Novel Approach Merging Biology Anmentioning
confidence: 99%
“…A cornerstone principle of cancer evolution is that genomic diversity acts as the substrate for natural selection in the inflamed colonic bowel; the more diverse the colonic epithelial cell population, the more likely a well-adapted, “dangerous” clone will be present, outcompete other clones, and evolve toward a malignant phenotype. This concept of evolutionary biomarkers, defined in terms of ecological diversity measures, has been repeatedly demonstrated to be predictive of neoplastic progression in patients with Barrett's esophagus ( 138 , 141 , 142 ).…”
Section: Evolutionary Biomarkers: a Novel Approach Merging Biology Anmentioning
confidence: 99%